Association between Arterial Stiffness and Serum L-Octanoylcarnitine and Lactosylceramide in Overweight Middle-Aged Subjects: 3-Year Follow-Up Study - Kim, Minjoo; Jung, Saem; Lee, Sang-Hyun; Lee, Jong Ho (PloS one, 2015)
Existing data on the association between being overweight and cardiovascular morbidity and mortality risk in adults are inconsistent. We prospectively and longitudinally investigated the effects of weight on arterial stiffness and plasma metabolites in middle-aged subjects (aged 40-55 years). A group of 59 individuals who remained within the range of overweight during repeated measurements over a 3-year period was compared with a control group of 59 normal weight subjects who were matched for age and gender. Changes in metabolites by UPLC-LTQ-Orbitrap mass spectrometry and changes in brachial-ankle pulse wave velocity (ba-PWV) were examined. At baseline, the overweight group showed higher BMI, waist circumference, triglyceride, free fatty acid (FFA), glucose, insulin, and hs-CRP, and lower HDL-cholesterol than controls. After 3 years, the changes in waist circumference, diastolic and systolic blood pressure (DBP and SBP), triglyceride, FFA, glucose, insulin, hs-CRP, and ba-PWV observed in the overweight group were significantly different from those in the control group after adjusting for baseline levels. Furthermore, the overweight group showed greater increases in L-octanoylcarnitine (q=0.006) and decanoylcarnitine (q=0.007), and higher peak intensities of L-leucine, L-octanoylcarnitine, and decanoylcarnitine. Multiple linear regression analysis showed that the change in ba-PWV was independently and positively associated with changes in L-octanoylcarnitine, lactosylceramide, and SBP, and with baseline BMI. Our results indicate that the duration of overweight is an important aggravating factor for arterial stiffness, especially during middle age. Additionally, an age-related increase in plasma L-octanoylcarnitine, lactosylceramide, SBP, and baseline BMI are independent predictors of increased arterial stiffness in middle-aged individuals.